KONDISI KEPALA KELUAGA MISKIN DI DESA TAMAN ASRI - Ardiansyah Ardiansyah; Buchori Asyik; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2014)
The objective of this research was to find out the condition of poor family heads in Taman Asri village of Purbolinggo sub district in Eastern Lampung district. This research used descriptive method. Population was 190 family heads, and samples were 38 family heads (20%). The result showed that the average width of field land owning of a poor family head was 0,21 ha. Status of field land of poor families in the first season of planting crop showed that 29 family heads (76,32%) had their own land and 9 family heads (23,68%) sharecrop, status of field land of poor families in the second season of planting crop showed that 29 family heads (76,32%) had their own land and 9 family heads (23,68%) rented the land. Numbers of poor family members were averagely 4 persons per family. Average annual income of each poor family was Rp 7.592.244 per family. The minimum basic poor family needs were only fulfilled 47,64% to 92,73%. 22 families (68,42%) were in poor conditions.Penelitian ini bertujuan untuk mengkaji kondisi kepala keluarga miskin di Desa Taman Asri Kecamatan Purbolinggo Kabupaten Lampung Timur. Metode yang digunakan metode deskriptif. Populasinya berjumlah 190 KK, sampel 20% (38 KK). Hasil penelitian ini menunjukkan bahwa: Rata-rata luas kepemilikan lahan sawah kepala keluarga miskin 0,21 ha. Status kepemilikan lahan sawah keluarga miskin pada periode penanaman pertama 29 KK (76,32%) milik sendiri dan 9 KK (23,68%) menyakap, status kepemilikan lahan sawah keluarga miskin pada periode penanaman kedua 29 KK (76,32%) milik sendiri dan 9 KK (23,68%) menyewa. Jumlah anggota keluarga miskin rata-rata 4 jiwa/KK. Pendapatan keluarga miskin rata-rata sebesar Rp 7.593.244 KK/tahun. Kebutuhan pokok minimum keluarga miskin terpenuhi 47,64% sampai dengan 92,37%. Sebanyak 22 KK (68,42%) berada pada kondisi miskin.Kata kunci: kepala keluarga, kondisi, miskin.